ANTIBACTERIAL ACTIVITIES OF DIFFERENT ANTISEPTIC SOAPS SOLD IN ABA ON STAPHYLOCOCCUS AUREUS FROM CLINICAL SAMPLES. - C. C., Ike, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The antibacterial activity of different types of antiseptic soaps on Staphylococcus aureusisolated from wound infections and eczematous lesions was evaluated. The samples were collectedfrom fifty individuals with wound and eczema infection within the age range of 9-73 years. Swabswere collected and streaked on appropriate agar and incubation temperature. Out of the fifty (50)individuals sampled, 25 persons were mostly infected with Staphylococcus aureus (50% ±1.05)followed by Pseudomonas aeruginosa (22% ±0.91), Staphylococcus epidermis (10% ±0.33) and theleast was Escherichia coli (18% ±0.72). This study revealed that Staphylococcus aureus isolated andsubcultured were sensitive to the three different antiseptic soaps. The zones of inhibition were highestin sample A with 25.0mm ±0.45 followed by sample B with 20.0mm ±0.98 and least in sample C with10.0mm ±0.65. The results showed that antiseptic soaps were effective against Staphylococcus aureusinvolved in wound and eczema infection in humans. Therefore, antiseptic soaps could be used incleaning the skin during time of hurt or cut, and should be used moderately by consumers to avoidirritation and resistance to pathogens.